IMPLEMENTASI PROGRAM DUTA WISATA DALAM MEMPROMOSIKAN POTENSI WISATA DI KABUPATEN TANAH DATAR - Fitra Liandi; Syamsir (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
This research is motivated by the occurrence of several problems in the Implementation of the Tourism Ambassador Program in promoting Tourism Potential in Tanah Datar Regency which is seen in the parameters of the Study in Tanah Datar Regency, which aims to determine the Work Implementation and Inhibiting Factors of the Implementation of the Tourism Ambassador Program in promoting Tourism Potential in the Regency. Flat Land. This research is a qualitative research with a descriptive approach that uses the source triangulation method. The results of the study show that the implementation of the Tourism Ambassador Program has not been optimal in promoting tourism potential in Tanah Datar Regency and there are still many inhibiting factors for the implementation of the tourism ambassador program in promoting tourism potential in Tanah Datar Regency.